Mathematics Education Lecturers’ Experiences of a Virtual Writing Retreat and its Impact on Publication Output - Mbhiza, Hlamulo Wiseman (Research in Social Sciences and Technology, 2024)
Departmental writing retreats for academics in higher education are one of the strategies used to enhance publication outputs and information sharing as well as the development of research discourse. Using a collaborative autoethnographic reflexivity approach, the aims of this consolidative analysis were to identify the attributes that the participants (seven Mathematics Education researchers) regarded as effective in the online writing retreat and examine the components of the writing retreat that facilitated publication output. This paper employs Wenger’s Community of Practice as the theoretical frame to critically evaluate reflective experiences from the online writing retreats. Fairclough’s Critical Discourse Analysis was used to analyse reflective experiences. The analysis unearthed many personal research needs and some of the key elements of the writing retreat that were regarded as conducive to fast tracking and advancing publication outputs. The elements I focus on in this paper are protected quality time and space to write; formation of a community of practice and attending to reviewers’ post-review comments. The contention is that researchers can achieve greater publication outputs for their departments and organisations during the writing retreats, particularly when provided with critical and formative feedback on their writing. Further research should be conducted to explore and examine researchers’ experiences of attending the writing retreats, especially using online platforms, as well as understanding the elements of writing retreats that advance the publication outcomes.